Faktor yang Memengaruhi Kualitas Hidup Penderita TB Paru di UPTD RS Khusus Paru Medan - Umraini Umraini; Ismail Efendy; Miskah Afriany (Jurnal Riset Hesti Medan, 2025)
Throughout the course of the disease, TB patients will experience several symptoms that interfere with their lives. Quality of life is a condition where a person gets satisfaction or enjoys their daily life. This study aims to analyze the factors that influence the quality of life of pulmonary TB patients at UPTD.Special Lung Hospital Medan.  This type of research is quantitative with a cross-sectional study design. This research was conducted at UPTD.Special Lung Hospital Medan in August-September 2024. The population in this study were all patients with pulmonary TB and were not compliant with treatment at UPTD.Special Lung Hospital Medan with a total of 558 people. The sample was determined by accidental sampling of 85 people. Data were analyzed univariately, bivariately and multivariate.  The results of the study showed that there was an influence of age (p=0.000), gender (p=0.000), compliance with taking medication (p=0.000), medical history (p=0.000), family support (p=0.000), smoking dependence (p=0.000) on the quality of pulmonary TB patients at the UPTD.RS Khusus Lung Medan. The most dominant factor was family support.  The conclusion is that there is an influence of age, gender, compliance with taking medication, medical history, family support, smoking dependence on the quality of pulmonary TB patients at the UPTD.RS Khusus Lung Medan. It is recommended that the results of this study can be an applicable concept for health workers to be able to improve health service efforts for pulmonary TB patients so that they can apply the rules that have been set, patients comply with undergoing treatment regularly and are good at taking care of themselves so that their disease is not transmitted to others.